2020
DOI: 10.1088/1755-1315/475/1/012005
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization of nitrogen compounds and hydroxyapatite: a slowly released fertiliser for water sustainability

Abstract: Ammonium sulfate (ZA) and nitrogen-phosphorus-potassium compound (NPK) are nitrogen-rich fertilisers commonly used by farmers. The fertilisers have high solubility in water, decay rapidly in wet soil and decompose into ammonia. Its lead into eutrophication phenomena and its absorption by crop roots becomes less effective. A facile and scalable method is developed to adsorb nitrogen-rich compounds into fish scale based powdered hydroxyapatite for slow-release fertiliser (SRF). Hydroxyapatite (HA) is a material … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Following the Korsmeyer–Peppas model, the release process is through diffusion and erosion. In contrast, the zero-order model indicates a constant release rate over time …”
Section: Mathematical Models For Nutrient Releasementioning
confidence: 99%
See 1 more Smart Citation
“…Following the Korsmeyer–Peppas model, the release process is through diffusion and erosion. In contrast, the zero-order model indicates a constant release rate over time …”
Section: Mathematical Models For Nutrient Releasementioning
confidence: 99%
“…In contrast, the zero-order model indicates a constant release rate over time. 22 A mathematical model has been developed to describe the controlled-release mode of urea from the coated fertilizer (rosin-coated urea, Figure 2) based on the experimental results. The mechanism of the release was determined based on the observation of the release from a pellet.…”
Section: Releasementioning
confidence: 99%
“…Hydroxyapatite [Ca10(PO4)6(OH)2] is a form of calcium phosphate that has been widely used as an implant material and has a composition similar to natural hard tissues such as bones and teeth. It has outstanding biocompatibility, osteoconductivity, and osteoinductivity [16,17]. In addition, many studies have shown that HA ceramics have no toxicity and inflammatory effect [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Hydroxyapatite is a form of calcium phosphate [Ca 10 (PO 4 ) 6 (OH) 2 ] that has been extensively utilized as an implant material and has a composition similar to natural hard tissues such as bone and teeth. It has exceptional biocompatibility, osteoconductivity, and osteoinductivity [7,8]. In addition, many studies have shown that HAp ceramics possess no toxicity and no inflammatory effect [9,10].…”
Section: Introductionmentioning
confidence: 99%